1985
DOI: 10.1177/0022427885022002002
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Informal Processing: A Look at Charge Bargaining and Sentence Reduction in Washington, D.C.

Abstract: Because the most important court decisions are not regulated by due process, any study concerned with discrimination should examine those informal processes. This study focuses on the processes of charge bargaining and sentence reduction. We identify criteria associated with these decisions and examine the differences in outcomes by gender of the defendant. It is found that dimensions of defense are the most important in determining a plea outcome favorable to the defendant, and that males fare better than fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 21 publications
1
12
0
1
Order By: Relevance
“…Although the seriousness of the current offense and prior record were the most important influences in determining charge reductions, a substantial amount of research found that individual characteristics also influenced charge reductions (see Albonetti, 1992;Bernstein, Kick, Leung, & Schulz, 1977;Farnworth & Teske, 1995;Figueira-McDonough, 1985;LaFree, 1980;McDonald, 1985;Miethe & Moore, 1986;Voit, 1987).…”
Section: Effect Of Offender Characteristics On Court Processingmentioning
confidence: 99%
“…Although the seriousness of the current offense and prior record were the most important influences in determining charge reductions, a substantial amount of research found that individual characteristics also influenced charge reductions (see Albonetti, 1992;Bernstein, Kick, Leung, & Schulz, 1977;Farnworth & Teske, 1995;Figueira-McDonough, 1985;LaFree, 1980;McDonald, 1985;Miethe & Moore, 1986;Voit, 1987).…”
Section: Effect Of Offender Characteristics On Court Processingmentioning
confidence: 99%
“…15 Based on this research, we can only conjecture that women are treated more severely than men in the decision to prosecute and that they may be more likely than men to enter guilty pleas (cf. Curran, 1983;Figueira-McDonough, 1985;Ghali and Chesney-Lind, 1986). Women also appear to be treated less severely than men in the pretrial release and final 15For a review of this research prior to 1980, see Nagel and Hagan (1982).…”
Section: Criminal Court Processing Of Offendersmentioning
confidence: 99%
“…Some studies find that plea bargaining favors the female defendants with more beneficial plea deals [16,17], while others find male defendants fare better [15]. Still, Bishop and Frazier's research finds the non-significant effect of defendant's gender on plea bargaining process.…”
Section: The Role Of Legal Characters In Plea Bargainingmentioning
confidence: 95%
“…Research [6,13,14] consistently documents that Blacks and Hispanics tend to be related to crime fear and are more likely to perceived as particularly threatening in the contemporary American community [13]. Specifically, argue that race is the most influential factor in the sentencing process and the court's offer of plea bargaining [15].…”
Section: The Role Of Legal Characters In Plea Bargainingmentioning
confidence: 99%